The smartness profile of selected European cities in urban management – a comparison analysis - Hajduk, Sławomira (Journal of Business Economics and Management, 2018)
The smart cities concept plays an important role in urban management worldwide as well as should be implemented with the participation of residents and with consideration for their needs. This study examines an analysis of the smartness diversity of European cities on the basis of the International Organization for Standardization 37120 norm dealing with sustainable development of communities. Cities with a higher level of certification exhibit more effective management and their residents show greater commitment to civic life. The assessment of the level of smartness was based on statistics collected by the World Council on City Data using Multidimensional Comparative Analysis. Hellwig’s (1968) synthetic indicators were used to create a ranking gauging the level of smartness of European cities which were classified into four groups. The investigation shows large disparities in the smartness of selected European cities.